Lower Jurassic felsic diatreme volcanism recognized in central Patagonia as evidence of along-strike rift segmentation. (March 2021) - Benedini, Leonardo; Pavón Pivetta, Cecilia; Marcos, Paulo; Gregori, Daniel A.; Barros, Mercedes; Scivetti, Nicolas; Costa dos Santos, Anderson; Strazzere, Leonardo; Geraldes, Mauro C.; de Queiroz Bernabé, Teodoro
Abstract: The early Jurassic volcanism of Central Patagonia covers an extensive area of 50, 000 km 2 where the volcanic deposits occur as isolated systems. The volcanic records form an elongated belt in which the composition, depositional and genetic features, show several differences along with its distribution. The Cañadón Chileno Complex (CCHC), located in the Río Negro province, provides the opportunity to evaluate and improve the knowledge about the Lower Jurassic volcanic stratigraphy and the Lower Jurassic regional setting of Central Patagonia. Based on the field and laboratory data developed in the present work, 22 lithofacies were recognized and grouped into eight facies associations. The continental sedimentary environments include alluvial fan deposits (FA 1), ephemeral deposits (FA 2), braided fluvial deposits (FA 3), alluvial plains, or over banks (FA 4), and lacustrine deposits (FA 9). On the other hand, the pyroclastic facies were separated according to the pyroclastic currents involved during the deposition; into fall-out, dilute, and density currents (FA 5, FA 6, and FA 7). Effusive andesitic feeders and lava-flows (FA 8) were also recognized. The stratigraphic data obtained in the present work allow proposing the existence of two felsic diatreme volcanoes in the CCHC records - described here as Southern and Northern Zone-, developed over a local subsided area, represented by an asymmetrical basin. Seven units were recognized and described in the CCHC (Units a, b, c, d, e, f, and g: unit (a) represents an initial stage of continental sedimentation recorded throughout the entire Complex. Unit (b) represents the upper felsic diatreme facies, in Southern Zone of the Complex, where debris flows are interbedded with massive lapilli-tuff deposits. Unit (c) consists of local andesitic lavas flows and feeder dikes, and the unit (d) consists of welded lapilli tuff deposits interpreted as the growth of the volcanic system. The Northern Zone evolves similarly with the felsic intra-diatreme deposits of unit (e). The unit (f) consisting of an effusive stage represented by extended andesitic lava flows. Finally, a deep lacustrine system is installed (unit g) that includes shallow and deep facies, with intercalations of local pyroclastic deposits. Also, new geochronological data (U-Pb zircon age of 188 ± 3 Ma) was determined to confirm and reinforce the correlation criteria between the different volcanic areas in Central Patagonia, indicating that the volcanism described here is synchronous with the Northern silica-rich calderas of the Garamilla Formation as well as the large andesitic volcanoes of the Lonco Trapial Formation located southward to the CCHC. The regional volcanism changes described, in the present work, are connected with the N-S rift segment limited by E-W regional transfer fault systems developed in continuity to the strike-slip structures of the La Esperanza area. Highlights: The Cañadón Chileno Complex (CCHC) is formed by sedimentary and volcanic units, assigned to a felsic diatreme volcanism. Includes conglomerates, sandstones, pyroclastic flows, effusive lavas, and lacustrine limestones. The age is 188.0 ± 3 Ma, and is coeval with other units of Patagonia.